Effectiveness of an mHealth intervention to increase adherence to triage of HPV DNA positive women who have performed self-collection (the ATICA study): A hybrid type I cluster randomised effectiveness-implementation trial - Silvina Arrossi; Melisa Paolino; Victoria Sánchez Antelo; Laura Thouyaret; Racquel E. Kohler; Milca Cuberli; Liliana Flores; Verónica Serra; Kasisomayajula Viswanath; Liliana Orellana (Elsevier, 2022)
Summary: Background: Human Papillomavirus (HPV) self-collection offered by community health workers (CHWs) during home visits has been hampered by low levels of triage Pap among HPV-positive women. We investigated effectiveness of a mHealth intervention to increase adherence to triage Pap. Methods: We conducted a hybrid type I cluster randomised effectiveness-implementation trial in Jujuy, Argentina. CHWs (clusters) were eligible if actively offering HPV self-collection and served at least 26 women aged 30 years and over. Women were eligible if they conducted self-collection and provided a mobile phone number. 260 CHWs were randomly allocated (3:2 ratio) to a multi-component intervention (Up to four SMS messages sent to HPV-positive women, and one SMS message to CHWs to prompt a visit of women with no triage Pap 60 days after a positive-test), or control group (Usual care: Women instructed to attend their health centre 30 days after HPV self-collection to pick-up results). The primary effectiveness outcome was percentage of HPV-positive women with triage 120 days after the HPV-test result. We evaluated implementation of the intervention using the RE-AIM framework. Findings: 221 CHWs (132 intervention, 89 control group) contacted 5389 women; and 5351 agreed to participate (3241 intervention, 2110 control group). In total 314/445 (70·5%) HPV-positive women of the intervention group had triage at 120 days after the HPV result, compared to 163/292 (55·1%) in the control group: 15·5% point improvement; 95%CI: 6·8-24·1; relative risk: 1·28; 95%CI: 1·11-1·48. 97·2% of women accepted the intervention and 86·9% of CHWs agreed to its adoption. Interpretation: The multicomponent mHealth intervention was effective in increasing the percentage of HPV-positive women who had triage Pap, allowing for many more women at risk of cervical cancer to receive timely follow-up. Funding: National Cancer Institute of the National Institutes of Health (USA) under Award Number R01CA218306.